ANALISIS FAKTOR RISIKO DAN PENANGANAN DEMAM BERDARAH DENGUE (DBD): SYSTEMATIC LITERATURE REVIEW - Linda Handayuni; Nia Watri Wahyuni; Vitratul Ilahi; Jeri Juliandi; Azifni Bhijannah; Siti Salsabila Nofrizal; Rafiona Anuggrah Illahi (Ensiklopedia of Journal, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia and globally. This study aims to analyze the risk factors and management of DHF through a Systematic Literature Review (SLR) approach. Literature was identified from PubMed, Scopus, Google Scholar, and ScienceDirect databases from 2021 to 2024. Fifteen relevant articles were selected based on inclusion and exclusion criteria using the PRISMA method. The findings indicate that the main risk factors for DHF include climate factors (temperature and humidity), environmental sanitation, individual behavior (3M Plus), sociodemographic characteristics, and community knowledge. Clinical management focuses on adequate fluid therapy, symptomatic treatment, and intensive monitoring to prevent dengue shock syndrome (DSS). Prevention through Mosquito Nest Eradication (PSN) and community empowerment remains the most effective strategy in controlling DHF. This study concludes that an integrated approach combining vector control, health education, and supportive policy is essential to reduce DHF morbidity and mortality in Indonesia.Keywords: Dengue Hemorrhagic Fever, Risk Factors, Management, Systematic Literature Review, Indonesia